A case report and literature review: osteomyelitis caused by community-associated methicillin resistant Staphylococcus aureus - Mehmet Uluğ; Celal Ayaz; Mustafa Kemal Celen (Journal of Infection in Developing Countries)
Osteomyelitis in adolescents is a serious disease with the potential for lifelong disability. The key to successful management is early diagnosis, including bone sampling for microbiological and pathological examination to allow targeted and long-lasting antibiotic therapy. Staphylococcus aureus is the most frequently isolated microorganism in these patients. Methicillin-resistant S. aureus (MRSA) is usually considered a nosocomial pathogen, but increasingly it is acquired in the community. We present a case of acute osteomyelitis caused by community-associated MRSA (CA-MRSA) who had never been hospitalized and had no other known risk factors for MRSA. The changing epidemiology of MRSA became evident when infections occurred in previously healthy patients without established risk factors. MRSA infections have been increasingly reported in pediatric patients, but they are uncommon in adults. Skin and soft tissue infections remain the most common manifestations of CA-MRSA infections. Glycopeptides can be used as initial therapy and oral trimetoprim-sulfamethoxazole as sequential therapy for these patients.